New records of Epallage fatime (Charpentier, 1840) in Macedonia (Odonata: Euphaeidae) - Matjaž Bedjanič; Damjan Vinko (Natura Sloveniae)
Formerly known from Macedonia only from two old records made in the southeasternmost part of the country, the species has been newly recorded on 20-VII-2008 at the Luda Mara stream south of Kavadarci (S Macedonia), on 24-VII-2008 at the Konska Reka stream west of Gevgelija (SE Macedonia) and on 26-IV-2010 at the Sermeninska Reka stream northwest of Gevgelija (SE Macedonia). At all localities, the species’ development has been confirmed. Its currently known distribution in Macedonia and the neighbouring countries is presented and a short zoogeographical discussion provided.